Development of the Early Childhood Emotional Perspective Taking Test (Edat): A Validity and Reliability Study - Tuncer, Murat; Gül, Emrah; Aslan, Durmuş (ISMAIL HAKKI MIRICI, 2024)
The aim of this research is to development a test measures the emotional perspective-taking abilities of early childhood children. Emotional perspective-taking is a social skill that involves accurately predicting the emotions of others by distinguishing them from one’s own emotions. The objective of this research is to better define this skill in early childhood and thus contribute to a better understanding of children’s levels of social-emotional development. The study group consists of 146 students aged 5-6. Data were collected through face-to-face interviews with children. Expert opinions were consulted during the research process to ensure the test’s content validity. Exploratory factor analysis (EFA), confirmatory factor analysis (CFA), item-total correlations and item analyses were used to establish construct validity. On the other hand, for the reliability of the test, KR-20, KR-21 and split-half reliability were used. The test which was developed for this purpose, consisted of a total of 13 items in two dimensions called “Confused-Scared” and “Happy-Sad” and a total of 13 pictures, one picture for each item. The research found that the Early Childhood Emotional Perspective Taking Test (EDAT) is a valid and reliable test for children aged 5-6 years. © 2024 by International Online Journal of Education and Teaching (IOJET).
Keywords: Early childhood development; Emotional perspective taking; Social skill; Test development